Computed tomographic diagnosis of incomplete palmar cortical (fatigue) fracture of the third metacarpal bone in two young adult endurance horses. (10th November 2017) - Beccati, F.; Cerocchi, A.; Conte, M.; Pilati, N.; Pepe, M.
Summary: Two young adult endurance horses were presented for investigation of sudden‐onset forelimb lameness during competition. Clinical examination revealed a severe forelimb lameness and pain on palpation of the proximal palmar metacarpal area. Initial radiographic survey of the affected forelimb was unremarkable in both cases. A week of box rest resulted in only a mild improvement in the lameness. A second radiographic examination did not reveal any significant abnormalities. In both cases, scintigraphic examination was suggested, but was declined by the owner, and the lameness had significantly improved after local infiltration of 3 mL of anaesthetic solution in the proximal suspensory region. Radiographic and ultrasonographic examinations of the carpus and proximal suspensory region were unremarkable in Case 2. Case 1 had increased thickness of the medial lobe of the proximal aspect of the suspensory ligament. A computed tomographic examination was performed and an incomplete longitudinal (fatigue) fracture of the proximal third metacarpal bone was detected. After 8 months of box rest and rehabilitation, re‐examination revealed resolution of the lameness in both cases. Advanced diagnostic imaging should be considered in young endurance horses with severe lameness during competition or training, in which radiographic and ultrasonographic examinations are unremarkable or do not explain the severity of the lameness. Computed tomography imaging is considered a useful diagnostic imaging technique to detect incomplete longitudinal palmar metacarpal cortical (fatigue) fractures due to its ability to provide excellent bone detail.